Saving beauty from the beast : how to protect your daughter from an unhealthy relationship - Crompton, Vicki; Kessner, Ellen Zelda (Boston : Little, Brown, 2003)
Offers advice for dealing with teen dating abuse, from stalking to physical assault, discussing the warning signs of an unhealthy relationship, steps that friends and parents can take, and ways to intervene effectively.
Prelude: Jenny's story. -- Part 1: Love that hurts. The roots of abuse in American society ; The black-and-blue soul : emotional abuse ; Prove that you love me : sexual abuse ; Kissed and choked on the same date : physical abuse ; Trapped and trying to tear free ; Why some boys choose to abuse. -- Part 2: What a parent can do. Warning signs : how to spot an abusive relationship ; Learning all you can about the relationship ; Early intervention ; Strategizing with common sense and creativity ; Actively confronting the violence ; Helping your daughter break away safely ; Terror/counterterror ; Aftermath of abuse : the healing journey ; If your child is a witness to abuse ; When you suspect your child may be an abuser ; A pound of prevention : how to bring up girls and boys to have relationships of trust and respect -- Epilogue: I confront Jenny's murderer in prison.
Includes bibliographical references (p. [246]-251) and index.
Keywords: Dating violence -- Prevention; Teenage girls -- Abuse of -- Prevention; Interpersonal relations in adolescence; Parent and teenager